2017
DOI: 10.2147/ndt.s132451
|View full text |Cite
|
Sign up to set email alerts
|

The genetic relationship between epilepsy and hemiplegic migraine

Abstract: Epilepsy and migraine are common diseases of the nervous system and share genetic and pathophysiological mechanisms. Familial hemiplegic migraine is an autosomal dominant disease. It is often used as a model of migraine. Four genes often contain one or more mutations in both epilepsy and hemiplegic migraine patients (ie, CACNA1A, ATP1A2, SCN1A, and PRRT2). A better understanding of the shared genetics of epilepsy and hemiplegic migraine may reveal new strategic directions for research and treatment of both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“… 14 SCA type 6 is caused by a CAG repeat in a calcium channel CACNA1A heavily expressed in the cerebellum. 92 Other observations that might also point to a trinucleotide repeat expansion or channelopathy underlying FCMTE include in Asian FCMTE pedigrees, progressively earlier onset of the disease with increasing severity in successive generations 19 21 ; presence of migraine 15 18 analogues to hemiplegic migraine with mutations in calcium channels 93 ; and the recognition that certain epilepsy syndromes are channelopathies. 45 , 94 Recently, an autosomal recessive form of FCMTE has been recognized with a single base pair deletion in CNTN2 , crucial for the stability of potassium channels.…”
Section: Discussionmentioning
confidence: 99%
“… 14 SCA type 6 is caused by a CAG repeat in a calcium channel CACNA1A heavily expressed in the cerebellum. 92 Other observations that might also point to a trinucleotide repeat expansion or channelopathy underlying FCMTE include in Asian FCMTE pedigrees, progressively earlier onset of the disease with increasing severity in successive generations 19 21 ; presence of migraine 15 18 analogues to hemiplegic migraine with mutations in calcium channels 93 ; and the recognition that certain epilepsy syndromes are channelopathies. 45 , 94 Recently, an autosomal recessive form of FCMTE has been recognized with a single base pair deletion in CNTN2 , crucial for the stability of potassium channels.…”
Section: Discussionmentioning
confidence: 99%
“…SNAP25 alters neurotransmitter release and calcium channel dynamics, which affects vesicle synapse accordingly [40]. It has been suggested that PRRT2 mutations impair SNAP25 function by altering Cav2.1 activity, which lead to neuronal hyperexcitability and subsequently cause epilepsy, PKD, or other paroxysmal movement disorders [41]. In addition to the relation between PRRT2 and SNAP25, many studies proposed that PRRT2 has postsynaptic roles in alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor signaling [42,43].…”
Section: Prrt2mentioning
confidence: 99%
“…1. Familial hemiplegic migraine and epilepsy CACNA1A, ATP1A2, SCN1A, and PRRT2 genes often contain one or more mutations in both epilepsy and hemiplegic migraine patients [8,21,41]. These shared mutations identified in epilepsy and migraine cases suggest that there is a common genetic basis for these conditions.…”
Section: Other Paroxysmal Movement Disorders and Epilepsymentioning
confidence: 99%
See 2 more Smart Citations